The Philippines an account of their people, progress, and condition - Campbell, Dauncey; Taft, William Howard; Roosevelt, Theodore (Massachussets The Plimpton Press, 1910)
As a sequel to the war with Spain we found ourselves in possession of the Philippines under circumstances which rendered it necessary to subdue a formidable insurrection which made it impossible for us with honour or with regard to the welfare of the islands to withdraw therefrom. The occasion was seized by the opponents of the President for trying to raise a new issue, on which they hoped they might be more successful than on the old. The clamour raised against him was joined in not only by many honest men who were led astray by a mistaken view or imperfect knowledge of the facts, but by all who feared effort, who shrank from the rough work of endeavour.
Electronic Reproduction.